On foot through Europe. A trail guide to the Briti - Evans, Craig (New York Quill, 1982)
Walking in Europe is a special experience. Wander the byways of the British Isles to see Hardrians Wall and Offas Dyke. For easy walking, hiking, backpacking, ski touring and climbing, youll have all information you need ar your fingerprints.
Keywords: Country Studies